HUMAN-AI COLLABORATION IN USER INTERFACE & USER EXPERIENCE EVLUATION USING DESIGN THINKING - Riski, Raulia; Hafsari, Alda Desmalia; Abdillah, Rosyid (Prosiding Seminar Nasional Teknologi dan Sistem Informasi, 2025)
The development of Artificial Intelligence (AI) technology has a significant impact on the evaluation and design of User Interface (UI) and User Experience (UX). This study aims to evaluate and redesign the website of Cafe XYZ, a café in Surabaya, by integrating a collaborative approach between humans and AI. The evaluation was carried out using the Think Aloud method to gather feedback from users, while ChatGPT-4o was involved in analyzing observation results and providing additional perspectives on the digital interface. The pre-evaluation findings revealed several issues, such as navigation difficulties, a confusing ordering flow, incomplete product information, and the absence of a self-service payment feature. These findings formed the basis for the redesign process using the Design Thinking method, which consists of five stages: Empathize, Define, Ideate, Prototype, and Testing. The proposed redesign emphasizes improvements in usability, service efficiency, and support for Cafe XYZ’s branding strategy to remain competitive in the digital era. This study demonstrates that human-AI collaboration can provide a more comprehensive perspective in UI/UX evaluation and produce solutions that are more adaptive to user needs. Thus, this research contributes significantly to the development of more user-friendly digital interfaces and serves as an example of applying Human-AI collaboration in empathy-based design processes.